Living values for a sustainable vocational orientation of university student - Do Manh Cuong; Do Thi My Trang (Journal of Technical Education Science, 2014)
Vocational education for Vietnamese high school students focuses on vocational orientation, for which the main activities include communication, recommendation, and advice for the student to choose an appropriate university and take a national entrance examination for it. Many parents believe that a university diploma is a guarantee for a bright future for their children. However, occupational activity takes most of the time of one’s life, in the sense that it is not only a physical need but also a means to fulfill their living values. This article aims to find a relation between the students’ living values and a sustainable vocational orientation. The results have shown that the higher the awareness of living values are, the clearer and more sustainable the vocational orientation should be. Moreover, it is necessary to change the vocational education thinking in Vietnam so that it should be begun earlier in terms of a strong collaboration of the family, the school and the society.